Football and cinema in the francoism: the political utilization of the sporting heroes in Franco´s Spain - Simón Sanjurjo, Juan Antonio (Historia y Comunicación Social, 2012)
The film industry during the 50´s took advantage of the huge impact of football in the Spanish society to produce a large number of films about this sport. One of the main attractions for the audience was the performance of the greatest football idols in several films: Ladislao Kubala and Alfredo Di Stéfano. Both footballers changed the history of their clubs, FC Barcelona and Real Madrid, and were tempted to starring some films. This paper aims to analyze the two films that have these football players like main actors (Los ases buscan la paz y Saeta rubia), to insist how the films show the image of the new sports hero. At the same time, the text try to discover what were the elements that shape the masculine model of success during the francoism.
Keywords: Football; history; cinema; a sport idol.